2011
DOI: 10.1097/hjh.0b013e32834436a7
|View full text |Cite
|
Sign up to set email alerts
|

In preeclampsia endogenous cardiotonic steroids induce vascular fibrosis and impair relaxation of umbilical arteries

Abstract: Background-Marinobufagenin (MBG), a bufadienolide cardiotonic steroid, induces cardiovascular fibrosis. Because levels of MBG in preeclampsia are increased, and anti-MBG monoclonal antibody reduces blood pressure (BP) in a rat model of preeclampsia, we hypothesized that in preeclampsia, elevated MBG levels would be associated with the development of fibrosis in feto-placental circulation and with impairment of vascular relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 31 publications
3
74
0
4
Order By: Relevance
“…Decrease of Fli-1, a nuclear transcription factor and a member of ETS family is implicated in MBG-induced fibrosis [11,12,18]. Fli-1 acts as a negative regulator of collagen-1 synthesis and it competes with another transcription factor, ETS-1, to maintain a balance between stimulation and repression of Col1a2 gene [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Decrease of Fli-1, a nuclear transcription factor and a member of ETS family is implicated in MBG-induced fibrosis [11,12,18]. Fli-1 acts as a negative regulator of collagen-1 synthesis and it competes with another transcription factor, ETS-1, to maintain a balance between stimulation and repression of Col1a2 gene [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in partially nephrectomized rats we demonstrated that development of cardiac fibrosis in the presence of elevated MBG levels was associated with decrease of Fli-1 [12]. In preeclampsia, which is also associated with elevated levels of MBG, fibrosis of umbilical arteries was accompanied by a dramatic reduction in the levels of Fli-1 [18]. In uremic rats a single administration of monoclonal anti-MBG antibody markedly reduced cardiac levels of collagen-1 in parallel with an increase in the levels of Fli-1, suggesting a causative relationship between MBG and Fli-1 [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations